TikTok Effect: Study Of Citayam Fashion Week - Zubaidi, Advan Navis (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
This study looks into how TikTok mediated the activities of its users in exploring fashion hobbies, particularly in the street event known as Citayam Fashion Week (CFW).  Previous studies looked into TikTok as a social media used for various purposes, including health information platforms, promotion channels, and education resources. This study aims to provide a distinct point of view of TikTok, specifically in the Indonesian context, by looking into TikTok as a social space for people from diverse backgrounds. Further, this study also will investigate how TikTok mediated its users to express their interests or hobbies, and how the fact will impact their social life. In doing so, I employ qualitative content analysis to examine online materials related to CFW. It includes videos uploaded on online platforms such as YouTube, TikTok, or mainstream media outlets. This study found that TikTok dissolves the boundaries between social classes. TikTok users from different backgrounds could express their ideas without the necessity of specific requirements. In addition, TikTok also economically affects people involved in its content, either actors on the TikTok video or people behind the scenes.